2010
DOI: 10.1158/1055-9965.epi-10-0295
|View full text |Cite
|
Sign up to set email alerts
|

Oxidatively Damaged DNA/Oxidative Stress in Children with Celiac Disease

Abstract: Background: Because patients with celiac disease face increased risk of cancer and there is considerable circumstantial evidence that oxidatively damaged DNA may be used as a marker predictive of cancer development, we decided, for the first time, to characterize oxidative stress/oxidative DNA damage in celiac disease patients.Methods: Two kinds of oxidatively damaged DNA biomarkers, namely, urinary excretion of 8-oxodG and 8-oxoGua, and the level of oxidatively damaged DNA in the leukocytes, as well as the le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 39 publications
4
31
0
Order By: Relevance
“…While comet assay or other methods used by other studies may be more direct measures of DNA damage, 8-OH-dG is an established marker of oxidative DNA damage and has been used in many studies of children (Dziaman et al, 2007; Svecova et al, 2009, Szaflarska-Poplawska et al, 2010). In this study, we did not monitor the extent of air pollution or ETS, which have been found to affect 8-OH-dG concentrations (Svecova et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…While comet assay or other methods used by other studies may be more direct measures of DNA damage, 8-OH-dG is an established marker of oxidative DNA damage and has been used in many studies of children (Dziaman et al, 2007; Svecova et al, 2009, Szaflarska-Poplawska et al, 2010). In this study, we did not monitor the extent of air pollution or ETS, which have been found to affect 8-OH-dG concentrations (Svecova et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Changes in vitamin E and antioxidant enzyme activities were observed also in circulating cells and plasma of patients [49,50,51,52,53,54,55] (Table 1). A decreased expression of the antioxidant and anti-inflammatory enzymes PON1 and PON3 mRNA was reported by Rothem et al in intestinal biopsy of celiac patients [56].…”
Section: Molecular Mechanisms On the Toxic Effects Of Glutenmentioning
confidence: 97%
“…Children with celiac disease, whether or not they are on a gluten-free diet, exhibit elevated urinary biomarkers of DNA damage (Zaflarska-Popawska et al , 2010). Human colon carcinoma cells exposed to peptides extracted from wheat responded with a sharp increase in the GSSG/GSH ratio (ratio of oxidized to reduced glutathione), a well-established indicator of oxidative stress (Rivabene, 1999).…”
Section: Cancermentioning
confidence: 99%